PENGARUH KOMPENSASI, KEPEMIMPINAN DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN PT. BANK SYARIAH MANDIRI TBK CABANG PEKANBARU - Dewi Patimah; Harlen Harlen; Susi Hendriani (Jurnal Ekonomi, 2016)
The population in this study as many as 110 people population in this study wereall employees of Bank Syariah Mandiri Branch Pekanbaru are some places inAdrees Soebrantas as many as 24 employees, at White Sands as many as 21employees, branched Sudirman 40 employees, and in Hope Kingdom at 25Employee. So total sample at the Syariah Mandiri branch PT.Bank Pekanbarunumber 110.Because as stated Arikunto taking the entire population beingsampled, while the sampling technique used in this study by census (Arikuto,2007: 115).From the results showed that: 1). There is a simultaneous influence betweenvariable compensation, leadership and work environment on employeeperformance. 2). A significant difference between compensation and performanceEmployee.3). There is a significant relationship between leadership andperformance Employee.4). There is a significant relationship between workenvironment with employee performance.To improve the quality of employees needs to be identified and grouped under theconditions required in awarding compensation, leadership style and workenvironment so that it can decide what to do. a) .Agar created efficiency of workof monitoring and explanation of how to work effectively. b) bonuses, should beincreased back and expected payments do not always late c). Leaders areexpected to work in the company Grama effective in working according to theprocedure. For the Working Environment need to maintain this condition, if theneed to do increase. In terms of working environment the company has been ableto provide the lay out of the den, and prsarana adequate facilities so thatemployees already feel quite comfortable. The communication links alreadyestablished employees are also quite good. Bosses are expected to be moreapproach to employees in order to create a harmonious working atmosphere,open and better in order to increase the performance ofemployees.